Penerapan Sistem Informasi Geografis Untuk Pemetaan Bengkel Tambal Ban di Kecamatan Selong Kabupaten Lombok Timur - Aris Sudianto; Nurhidayati Ida; Lalu Kerta Wijaya (Fakultas Teknik Universitas Hamzanwadi, 2020)
The existence of a realtime, fast, and accurate information is important for human survival at this time. The data and information needed must be easily and effectively accessed by various interested parties. Along with advances in computer and information technology today, GIS (Geographic Information System) is a technology that is developing both desktop and online. Many companies use this technology to advance the company and make the company better serve the community, besides this GIS technology can be utilized to advance small and medium businesses, especially in terms of location information as well as tire repair businesses that really need a touch of technology so that the existence The business is better known by the wider community, the number of tire repair shops spread so much in the District of Selong makes this business need to get more attention, considering this type of business has a very important role for the smooth transportation of the community. For this reason, the role of technology is very important in order to enable these entrepreneurs to move forward in advancing the tire tapping business. With the mapping technology, it is expected that the public will be able to find out all locations of the tire patch workshops spread across the Selong sub-district, so that when in the Selong area, the public does not need to worry if the motor / car has a broken tire, because the location of the tire repair shop is accessible from anywhere as long as connected to the internet. Based on the above problems, the author raises the theme of the research Application of Geographic Information Systems for Mapping Tire Repair Workshop in Selong District, East Lombok RegencyDOI : 10.29408/jit.v3i1.1824